Investigation of Escherichia coli Tat (twin arginine translocase) transport in vitro - Yong, S (2011)
The Twin arginine translocase (Tat) system catalyzes movement of folded proteins across the cytoplasmic membrane of bacteria and the thylakoid membrane of plant chloroplasts. This transport process requires energy in the form of the transmembrane proton motive force (PMF). The Tat system can be studied in vitro using inner membrane vesicles (IMVs) from E. coli overproducing the Tat components, TatA, TatB and TatC. However, the transport efficiencies of current in vitro Tat transport assays are low. In this work, current in vitro Tat transport assays were compared and parameters that affect transport efficiencies were identified. Mild French press treatment of IMVs resulted in larger IMVs with higher transport efficiencies. Chloride ions were shown to inhibit Tat transport in vitro. Generation of a PMF by the activity of ATP synthase gave higher transport efficiencies than generating a PMF by NADH respiration. This understanding was applied to develop an optimized in vitro Tat transport assay that showed a higher transport efficiency than currently published methods. Fluorescently labelled Tat substrates were developed to allow quantitative analysis of Tat transport. The transport of the purified native Tat substrate, CueO into IMVs was characterized using the optimized in vitro Tat transport assay. It was shown that the proton concentration (ΔpH) component of the PMF was sufficient to support Tat transport in vitro. It was observed that transport of CueO ceased in a time-dependent manner in the in vitro Tat transport assays. This loss of transport efficiency could be due, at least in part, to the presence of a PMF since transport efficiency was reduced when IMVs were pre-energized. Substrates for future in vitro single molecule fluorescence microscopy studies of the Tat transport were developed in this work. One of the substrates is fluorescently labelled CueO. The second substrate is the native Tat substrate alkaline phosphatase PhoX from Vibrio fischeri which was able to cleave the fluorogenic compound AttoPhos® and can thus be used as an enzymatic reporter of Tat transport. The structure of a native Tat substrate from Pseudomonas fluorescens, PhoX, was solved by X-ray crystallography at a resolution of 1.4Å. PhoX is a monomeric six blade β propeller with two α-helical bundle subdomains. PhoX was shown to have optimum activity at pH8.0. PhoX has a novel catalytic site which requires two Fe3+ (including a Cys-coordinated Fe3+) and three Ca2+ as cofactors. Mutagenesis studies showed that all the metal ions are required for the integrity of the active site. Co-crystallization of PhoX with vanadate, an inhibitor of PhoX which mimics the transition state, showed that hydrolysis of phosphomonoesters does not involve formation of a covalent phosphoenzyme intermediate. Instead, dephosphorylation of substrates is proposed to occur via a SN2 reaction with OH- as the attacking nucleophile.